Addressing demographic differences in servicescape influence among department stores’ patrons in Malaysia / Zuraini Alias, Mokhtar Abdullah - Abdullah, Mokhtar (Faculty of Business and Management, Universiti Teknologi MARA, Puncak Alam Campus, 2017)
While numerous published works have extensively examined servicescape models and its linkage to loyalty, not many have systematically examined the influence of demographic factors specifically on servicescape in the context of department stores. The purpose of this study is to examine whether servicescape of department stores have specific influence on six demographic characteristics (age, gender, income, race, education and occupation). A mall intercept method was conducted by administering 560 questionnaires across 5 regions in Malaysia. The results indicate that age and income are strongly associated with servicescape (differences in perception as well as experiences on servicescape), while gender, race, occupation, education and occupation are not. Additionally, it was found that older consumers possess different motives on servicescape implications compared to the younger consumers. The results indicated that patrons to department stores have different perception on servicescapes especially among the high income and younger age groups. The findings will enable retailers to understand the implications of customers’ experiential values and personality in line with the demographic characteristics affecting the servicescape offerings. This could lead to better servicescape development strategies to create unique in-store environments to enhance shopping experiences and therefore, result in more satisfied shoppers.